2007
DOI: 10.1080/17486020701474962
|View full text |Cite
|
Sign up to set email alerts
|

DEM analysis of angular ballast breakage under cyclic loading

Abstract: Railway ballast particles undergo significant amount of breakage under repeated train load. Breakage of ballast particles, especially highly angular fresh ones, causes an increase in settlement, contributing to track degradation. The quantitative analysis of the influence of breakage on the stress-strain properties of ballast can be performed either experimentally or numerically. Numerical modeling has the advantage of simulating ballast breakage 10 subject to various types of loading and different boundary co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(40 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…-relationship between ballast aggregate degradation, additionally cohesion, inner friction angle and the water permeability of material and its layer was investigated [29], -angularity breakage phenomenon [15,37], -relationship of PSD of ballast material and its mechanical abrasion was examined, and newly PSD was improved and induced according to more real loading conditions [26,56], -volumetric and axial deformations, additionally particle breakage were measured by laboratory triaxial testing regarding to different stress values (main stresses and deviator stresses) [8,37], -a special method was developed to be able to define PSD of ballast aggregate with using of ground penetrating radar (GPR) [4,55], -at DEM simulations more real particle shape generation method was researched and DEM models were validated [11,37,53], -laboratory and field tests were performed with and without geosynthetic inclusions, ballast material degradation was measured [10,15,38,46], -tyre derived aggregates (TDA) were tested in case of sand fouled ballasted tracks [18], -ballast grain degradation due to ballast tamping was investigated [1,17], -ballast structure with adhesive material was examined [30].…”
Section: Methodsmentioning
confidence: 99%
“…-relationship between ballast aggregate degradation, additionally cohesion, inner friction angle and the water permeability of material and its layer was investigated [29], -angularity breakage phenomenon [15,37], -relationship of PSD of ballast material and its mechanical abrasion was examined, and newly PSD was improved and induced according to more real loading conditions [26,56], -volumetric and axial deformations, additionally particle breakage were measured by laboratory triaxial testing regarding to different stress values (main stresses and deviator stresses) [8,37], -a special method was developed to be able to define PSD of ballast aggregate with using of ground penetrating radar (GPR) [4,55], -at DEM simulations more real particle shape generation method was researched and DEM models were validated [11,37,53], -laboratory and field tests were performed with and without geosynthetic inclusions, ballast material degradation was measured [10,15,38,46], -tyre derived aggregates (TDA) were tested in case of sand fouled ballasted tracks [18], -ballast grain degradation due to ballast tamping was investigated [1,17], -ballast structure with adhesive material was examined [30].…”
Section: Methodsmentioning
confidence: 99%
“…In this range, the volumetric behaviour changes from mainly dilation at low confining pressure to compression with the increasing confining pressure. Past experimental and DEM studies on coarse granular materials conducted at University of Wollongong have shown that in the early dilation stage, particle degradation is mainly associated with the breakage of sharp corners of the angular particles, and then followed by a stage where densification (overall compression) occurs with much less breakage (Indraratna et al, 2005 andHossain et al 2007). However, as the confining pressure is increased considerably, dilation is prevented and the particle assembly undergoes increased compression and associated breakage occurs across the middle part of the grains and not just at the corners (Indraratna et al 2010 andIndraratna et al 2014).…”
Section: Stress-strain Behaviour and Associated Breakagementioning
confidence: 99%
“…Recycled ballast was collected from a recycled plant commissioned by RailCorp at their Chullora yard near Sydney. A physical examination indicated (Hossain et al 2007). …”
Section: Field Tests On Instrumented Track At Bullimentioning
confidence: 99%
“…confining pressure and angularity of the ballast particles. Hossain et al (2007) developed a numerical model using the Discrete Element Method (DEM) to investigate the effect of breakage on the stress-strain behaviour of ballast under different confining pressures. Irregularly shaped particles of ballast were considered and their angularity was modelled by clumping upto nine circular particles together to form single particles of twelve different shapes.…”
Section: Dmentioning
confidence: 99%
See 1 more Smart Citation